2012
DOI: 10.1002/hep.25524
|View full text |Cite
|
Sign up to set email alerts
|

Reply

Abstract: According to the recently released American Association for the Study of Liver Diseases (AASLD) guidelines for the treatment of hepatitis C virus (HCV) genotype 1 chronic infection, 1 in treatment-naïve subjects the association of boceprevir or telaprevir with peginterferon-alpha and ribavirin is strongly recommended as the optimal therapy. In patients treated with boceprevir, peginterferon, and ribavirin, a response-guided treatment schedule was established at week 8, through the assessment of HCV RNA level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…Using CCR:HCV laboratory and prescription data from all 130 VHA facilities, we produced reports of facility, regional (the VA system is divided into 21 regions, or veterans integrated service networks), and national level populations identifying the number of veterans with HCV genotype 1 infection who were in need of treatment as determined by a detectable HCV viral load, as well as those who appeared to be eligible candidates based on the indication for therapy and expected contraindications. 8 Using pharmacy records to track historical use of peginterferon plus ribavirin, we constructed models of drug uptake using historical caseloads for VA HCV treatment and projected rates of new treatment caseloads over time. The models assumed the following: the numbers of veterans with HCV in care would remain stable; only genotype 1 HCVinfected patients would be eligible for treatment; both treatment naïve and experienced patients would be eligible; patients with contraindications to peginterferon or ribavirin (based on VA comorbidity data in HCV-infected veterans) would remain ineligible for treatment; and yearly HCV treatment rates would range from 5% to 25% of those eligible based on historical VA treatment rates.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…Using CCR:HCV laboratory and prescription data from all 130 VHA facilities, we produced reports of facility, regional (the VA system is divided into 21 regions, or veterans integrated service networks), and national level populations identifying the number of veterans with HCV genotype 1 infection who were in need of treatment as determined by a detectable HCV viral load, as well as those who appeared to be eligible candidates based on the indication for therapy and expected contraindications. 8 Using pharmacy records to track historical use of peginterferon plus ribavirin, we constructed models of drug uptake using historical caseloads for VA HCV treatment and projected rates of new treatment caseloads over time. The models assumed the following: the numbers of veterans with HCV in care would remain stable; only genotype 1 HCVinfected patients would be eligible for treatment; both treatment naïve and experienced patients would be eligible; patients with contraindications to peginterferon or ribavirin (based on VA comorbidity data in HCV-infected veterans) would remain ineligible for treatment; and yearly HCV treatment rates would range from 5% to 25% of those eligible based on historical VA treatment rates.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…[4][5][6][7] Despite advances in efficacy, evidence suggested that boceprevir-or telaprevir-based regimens would be more difficult to manage because of complex treatment algorithms, higher pill burden, complicated drug interactions, and adverse effects, particularly anemia. [8][9] Safety and effectiveness data in real-world populations, such as veterans, with comorbidities or relative contraindications upon which to make formulary decisions did not exist. Demand for these agents was great given the landmark changes in response, yet the baseline characteristics of the clinical trial populations in whom these agents were evaluated were substantially different from those of the VA HCV-infected population.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…The addition of PIs to the previous standard of care, Peg-interferon (PegIFN) and ribavirin (RBV), has boosted the sustained virologic response (SVR) to approximately 75% in treatmentnaïve patients [1] and [2]. Echoing these results, scientific communities [3] and [4] and governmental health care organizations [5] recommended triple therapies with PegIFN, RBV, and PIs as the new standard of care for genotype 1 untreated and previously treated patients. The therapeutic advances with triple therapies came at the expenses of increased adverse effects, significant drug-drug interactions, and induction of viral mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the only available therapy was interferon for 6 to 24 weeks (3 million international units) or the same intravenous dose of interferon for 4 to 7 weeks (105). Since 2001, pegylated interferon α with ribavirin has shown favorable results against genotype 2 and 3 (106).…”
Section: Disease Managementmentioning
confidence: 99%